State-of-the-Art Authentication Measures in Satellite Communication Networks: A Comprehensive Analysis - Suhaimi, Nur Hanis Sabrina; Kamarudin, Nazhatul Hafizah; Khalid, Mohd Nor Akmal; Tahir, Ibrahim; Mohamed, Muhammad Amir Afiq (IEEE access, 2024)
Satellite communication (SatCom) is essential in modern telecommunication infrastructure, providing global connectivity and overcoming limitations of the terrestrial network. With the emergence of vertical heterogeneous networks integrating terrestrial and non-terrestrial networks, authentication becomes crucial to address security challenges, especially in low Earth orbit SatCom. This review comprehensively explores the authentication mechanisms, challenges, and future research directions to offer a holistic view of authentication in satellite communication networks. This study adopts a systematic approach that follows five phases: research planning, search execution, study selection, data classification, and study mapping. Explores recent research on various authentication schemes in SatCom, focusing on fundamental research questions to uncover the complexities associated with authentication in this domain. Existing authentication protocols are analyzed by using a multi-criteria classification approach to highlight their strengths, weaknesses, and security implications. By investigating current authentication systems in SatCom and identifying emerging trends, this review offers a roadmap for future research, providing valuable insights for practitioners, policymakers, and researchers. Enhances understanding of SatCom authentication complexity, laying the groundwork for resilient security measures crucial to the sustainable advancement of Space-Ground network technology.